(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Ulugbek Hamdam penned the situation that was tormenting many people at the time of writing the novel, and which had passed or was passing in the hearts of many people. Dilmurod Kuronov explains this situation as follows: "Equilibrium" was born as a novel that was very relevant in terms of the topic and was written at the time. The second side of the issue is how the current topic is covered. The novel is largely autobiographical.